131k views
2 votes
Evaluate the expression 12-3y\2 + y(2y-4\y) for y =3​

1 Answer

4 votes

Answer:

43/2

Explanation:

Evaluate 12 - (3 y)/2 + y (2 y - 4/y) where y = 3:

12 - 3 y/2 + y (2 y - 4/y) = 12 - 3×3/2 + 3 (2×3 - 4/3)

Hint: | Express -3×3/2 as a single fraction.

-3×3/2 = (-3×3)/2:

12 + (-3×3)/2 + 3 (2×3 - 4/3)

Hint: | Multiply 2 and 3 together.

2×3 = 6:

12 - (3×3)/2 + 3 (6 - 4/3)

Hint: | Multiply -3 and 3 together.

-3×3 = -9:

12 + (-9)/2 + 3 (6 - 4/3)

Hint: | Put the fractions in 6 - 4/3 over a common denominator.

Put 6 - 4/3 over the common denominator 3. 6 - 4/3 = (3×6)/3 - 4/3:

12 - 9/2 + 3 (3×6)/3 - 4/3

Hint: | Multiply 3 and 6 together.

3×6 = 18:

12 - 9/2 + 3 (18/3 - 4/3)

Hint: | Subtract the fractions over a common denominator to a single fraction.

18/3 - 4/3 = (18 - 4)/3:

12 - 9/2 + 3 (18 - 4)/3

Hint: | Subtract 4 from 18.

| 1 | 8

- | | 4

| 1 | 4:

12 - 9/2 + 3×14/3

Hint: | Express 3×14/3 as a single fraction.

3×14/3 = (3×14)/3:

12 - 9/2 + (3×14)/3

Hint: | Cancel common terms in the numerator and denominator of (3×14)/3.

(3×14)/3 = 3/3×14 = 14:

12 - 9/2 + 14

Hint: | Put the fractions in 12 - 9/2 + 14 over a common denominator.

Put 12 - 9/2 + 14 over the common denominator 2. 12 - 9/2 + 14 = (2×12)/2 - 9/2 + (2×14)/2:

(2×12)/2 - 9/2 + (2×14)/2

Hint: | Multiply 2 and 12 together.

2×12 = 24:

24/2 - 9/2 + (2×14)/2

Hint: | Multiply 2 and 14 together.

2×14 = 28:

24/2 - 9/2 + 28/2

Hint: | Add the fractions over a common denominator to a single fraction.

24/2 - 9/2 + 28/2 = (24 - 9 + 28)/2:

(24 - 9 + 28)/2

Hint: | Evaluate 24 + 28 using long addition.

| 1 |

| 2 | 8

+ | 2 | 4

| 5 | 2:

(52 - 9)/2

Hint: | Subtract 9 from 52.

| 4 | 12

| 5 | 2

- | | 9

| 4 | 3:

Answer: 43/2

User Soyini
by
4.5k points